The Effectiveness of Ice-Breaker Activity to Improve Students’ Speaking Skill of The Third Semester Students of English Department Students of FKIP UKI Toraja - Selvy Panggua (UKI TORAJA, 2016)
This research was aimed at investigating the effectiveness of Ice-BreakerActivity in improving students’ Speaking skill and the students’ perceptionstowards the use of Ice-Breaker activity in improving speaking skill of thethird semester students of English Department of FKIP UKI Toraja.A quasi experimental design was employed with one class of the thirdsemester students of English Department of FKIP UKI Toraja. Sampleswere selected by using cluster sampling method. The data were obtainedthrough oral test and a questionnaire. The Speaking assessment wascovering pronunciation, vocabulary, grammar, fluency and self-confidence.The findings were analyzed statistically using independent t-testprocedure.The findings showed that the value of t-test in experimental class was higherthan the value of t-table(value of t 3.57 > value of t table 2.021).Furthermore, the students‘ perception towards Ice-Breaker Activity was95.2% students agreed that this technique could help them to increse theirSpeaking skill.The statistical computation showed that Ice-Breaker Activity was noteffective in improving the students’ Speaking skill but the students havepositive perception towards the use of Ice-Breaker Activity in improvingtheir speaking skill. Designing the learning purpose appropriately whichconsiders students’ needs and language level may ease lecturer to usethe the Ice-Breaker Activity in improving students’ Speaking skill. Thelecturer may try to take advantage of Ice-Breaker Activity to beutilized in their classroom activities to conduct an effective andinteresting learning atmosphere in the classroom.